2011
DOI: 10.1007/s10120-011-0095-4
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of gastric perforation in the setting of gastric cancer

Abstract: Background Gastric perforation is a rare presentation of gastric cancer and is thought to be a predictor of advanced disease and, thus, poor prognosis. Guidelines do not exist for the optimal management strategy. We aimed to identify, review, and summarize the literature pertaining to perforation in the setting of gastric cancer. Methods A qualitative, systematic review of the literature was performed from January 1, 1985, to January 1, 2010. Searches of MEDLINE, EMBASE, and the Cochrane Central Register of Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 11 publications
2
35
0
2
Order By: Relevance
“…Tsujimoto et al [2] showed that there were no significant differences in Surgery for perforated gastric cancer 583 the recurrence rate and pattern between perforated and nonperforated gastric cancer. Several other publications also showed that peritoneal contamination due to perforation did not adversely affect survival in perforated gastric cancer [5,6,124]. Second, uneven levels of diagnosis and treatment at different centers might have affected the results of this study.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Tsujimoto et al [2] showed that there were no significant differences in Surgery for perforated gastric cancer 583 the recurrence rate and pattern between perforated and nonperforated gastric cancer. Several other publications also showed that peritoneal contamination due to perforation did not adversely affect survival in perforated gastric cancer [5,6,124]. Second, uneven levels of diagnosis and treatment at different centers might have affected the results of this study.…”
Section: Discussionmentioning
confidence: 75%
“…Regardless of whether one-stage or two-stage gastrectomy is employed, the most important goal of surgical treatment for perforated gastric cancer is to achieve curative R0 resection, the same as in non-perforated common gastric cancer [6]. When curative resection was possible, the median survival time was 75 months and the 5-year survival rate was about 50 % in perforated gastric cancer [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations